CONSORT and the internal validity of randomized controlled trials in Female Pelvic Medicine. Issue 7 (14th July 2015) - Koch, Marianne; Riss, Paul; Umek, Wolfgang; Hanzal, Engelbert
Abstract : Aims: To investigate authors' adherence to the CONSORT reporting guideline for randomized controlled trials (RCTs) in the sub‐specialty Female Pelvic Medicine and to detect any changes in adherence between the years 2008 and 2013. Methods: Bibliometric study. We included Female Pelvic Medicine RCTs published in 2008 and 2012–2013 in 10 journals. Full‐text versions of RCTs for the inclusion of the CONSORT checklist items Randomization, Allocation, Blinding, and Participants' flowchart were screened. Each CONSORT checklist item was categorized for each included RCT as either "complete reporting", "insufficient reporting", "no reporting, " or "not applicable". We screened the "Instructions to authors" for the requirement to adhere to CONSORT. Results: We included 94 Female Pelvic Medicine RCTs for analysis. Most RCTs in 2008, 2012, and 2013 were published by IUJ (n =n39), followed by NAU (n = 13), GREEN (n = 12), European Urology (n = 8), FMPRS (n = 6), AJOG (n = 4), Urology (n = 3), NEJM (n = 3), Lancet (n = 1), and BJOG (n = 1). Proportion of RCTs in the category "complete reporting" comparing 2008 and 2013 was (47 and 70%) for Randomization, (18 and 45%) for Allocation, and (29 and 52%) for Blinding; a flowchart was presented in (71 and 91%). The increase was not statistically significant in any of the investigated CONSORT items. Conclusions: Complete reporting of Female Pelvic Medicine RCTs has increased between 2008 and 2013. However, there are still a relevant number of published RCTs, which do not fulfill these criteria. Reporting according to the CONSORT guidelines should be further encouraged to improve internal validity of Female Pelvic Medicine RCTs. Neurourol. Urodynam. 35:826–830, 2016 . © 2015 Wiley Periodicals, Inc.